Practical applications of artificial intelligence in the development of predictive models: A case study with ChatGPT - Calderón Carrillo, José Iván (LACCEI, 2025)
The main objective of the research is to present the role that artificial intelligence applications play in the quantitative analysis required for the development of predictive models and the support they provide in this process. The aim is to understand how these applications can influence the field of business management and continuous improvement within organizations. To this end, a practical example of the use of an artificial intelligence application for the development of a predictive model is shown, comparing it with the development of the same predictive model under a conventional method, with the main results being that artificial intelligence applications facilitate and speed up the data analysis process for correct business decision making.